The Research Landscape of Environmental Education for Sustainable Development in Basic Education: A Bibliometric Analysis - Zhiteng Yan; Mohd Hanafi Mohd Yasin; Mohd Sofian Omar Fauzee; WanSuraya WanNik (Eastasouth Institute, 2025)
Environmental education focused on sustainable development is essential for creating a sustainable future, since it provides individuals with the knowledge, skills, and attitudes necessary to address complex environmental issues. Such capabilities should be emphasized from the beginning of basic education. Therefore, it is essential to systematically explore research on environmental education for sustainable development in basic education. Using bibliometric methods, this study analyzed 391 scholarly articles retrieved from the core collection of Web of Science databases with the aid of VOSviewer. Identified key topic areas, influential publications, and emerging trends in the field through co-word and co-citation analysis. The co-word analysis revealed five primary clusters, whereas the co-citation analysis uncovered six principal clusters. The findings indicate a burgeoning academic interest in environmental education for sustainable development. The quantity of studies has consistently risen, and the subjects addressed have progressively broadened from fundamental environmental awareness to the development of transdisciplinary skills and the establishment of systematic thinking. Nonetheless, additional comprehensive research is required to thoroughly elucidate this field of study. This study has demonstrated useful insights for educators, policymakers, and academics to enhance the effective and comprehensive integration of sustainable development ideas into basic education.